IMPLEMENTASI KONSEP KAFA’AH TERHADAP KETAHANAN KELUARGA - Muhamad Amrozi; Sofian Syaiful Rizal (LPPM STAI Muhammadiyah Probolinggo, 2025)
The concept of kafa'ah in marriage emphasizes equality and harmony between prospective husband and wife, especially in terms of religion, morals, education, and social status. This study aims to examine the views of the people of regency on the concept of kafa'ah and its application in choosing a life partner. Through qualitative methods by interviewing community leaders and several families, it was found that the majority of the community considered equality in educational background and religious values ​​as the main factors in building household harmony. In addition, they prioritize the same goals in life, especially in the spiritual aspect, compared to material factors. The results of the study also show that in some cases, marriages that are not based on the principle of kafa'ah tend to experience problems, such as disputes in the household. One example is the experience of Mr. Imron, who faced disharmony due to significant differences in religious values ​​and life vision with his partner. This study concludes that the application of the concept of kafa'ah in the aspects of religion, morals, and common goals in life has an important role in maintaining family resilience, reducing household conflicts, and achieving a harmonious and sustainable marriage. Keywords: Kafa’ah, Marriage, Family Resilience, Sociology of Law